Student-Centeredness by Knowledge Sharing: An Effective Learning in Madrasah - Muhammad Munif; Hasan Baharun; Zamroni Zamroni; Adilatul Himmah Fiqiyadatil Ummah (STAI Hubbulwathan Duri, 2022)
This study analyzes effective learning management through student-centred learning assisted by knowledge sharing at an Islamic-based junior high school in Krejengan. The qualitative case study method was employed in this investigation. In order to gather information, the researchers used interviews, observations, and documentation. When it comes to data analysis, there are several steps to follow: data gathering, data reduction, data presentation, and conclusions as study findings. The results showed that effective learning management with a student-centred learning approach assisted by knowledge sharing at an Islamic-based junior high school in Krejengan was carried out through the stages of planning, implementing, and evaluating systematically by the teacher to obtain maximum effective learning outcomes. Student-centred learning approach assisted by knowledge sharing designed in such a way can make learning effective. This can be used as a reference by educators in creating effective learning to achieve optimal learning objectives.